The Changing Meanings of Neighborhood in Modern Istanbul - (:unkn) unknown (My University, 2021)
Departing from the Ottoman-Turkish concept of mahalle (neighborhood) and its transformation, this article endeavors to discuss how the local people react to the socio-economic changes that came along the revitalization processes in İstanbul in the last 10 years. The study departs from a field work that has been conducted in Rasimpaşa neighborhood in Kadıköy, located at the Asian part of Istanbul, where there seems to be an ongoing process of revitalization, which started in 2010 with the partnership of The Foundation for the Protection and Promotion of the Environment and Cultural Heritage [ÇEKÜL] and Kadıköy Municipality. Rasimpaşa neighborhood constitutes a good example for old mahalle tradition since it preserved the Ottoman heritage and it is officially under the urban protection. Today it seems to preserve the characteristics of the “mahalle culture” that is embraced by the migrant families who came to İstanbul from Anatolian cities and who got localized here in time. Moreover, Rasimpaşa accommodates newcomers such as university students, international visitors (Erasmus students, upper middle-class artists, musicians, travelers). The question of the research has a simple focus: How do the local shopkeepers perceive the recent changes in the neighborhood and what are their reactions regarding the past present and future of neighborhood. it is assumed that the locals in Rasimpaşa would wel-come the revitalization process that would increase the visitors/tourists/customers. According the findings of the field work most of the local shopkeepers perceive the process in a negative way due to the decay of traditional values as well as decay of old neighborhood lifestyle. Hence this study tries to address the social implications of the revitalization process by demonstrating how and why local people respond to this transformation.

Makale, Türk ve Osmanlı kültüründeki mahalle kavramından yola çıkarak mahalle kavramının dönüşümünü ve son on yılda İstanbul’daki kentsel canlandırma projelerinin getirdiği sosyo-ekonomik değişimleri yerel esnafın gözünden görmeyi amaçlamıştır. Çalışmanın mekanı İstanbul’un Anadolu yakasında bulunan Kadıköy Rasimpaşa mahallesidir. Bu mekanın seçilmesinin temel nedeni Rasimpaşa’nın Belediye ve Çevre ve Kültür Değerlerini Korumave Tanıtma Vakfı [ÇEKÜL] işbirliği ile 2010 yılında başlatılan canlandırma projesinin parçası olmasıdır. Rasimpaşa mahallesiOsmanlı mirasını koruması ve resmi olarak koruma altında olması nedeniyle dönüşen“mahalle” kavramı için iyi bir örnektir. Anadolu kentlerinden gelip zaman içinde burada yerleşik hale gelen göçmen aileler, mahalle kültürünün korunmasında önemli bir rol oynamıştır. Günümüzde Rasimpaşa’nın nüfusuna her geçen gün üniversite öğrencileri, dış ülkelerden gelen gezginler, üst orta sınıf kentliler, sanatçılar eklenmektedir. Makalenin araştırma sorusu, mahalle sakinlerinin yaşadıkları canlandırma sürecini nasıl algıladıkları ve mahallenin geçmişi, bugünü ve geleceği hakkındaki görüşleridir. Araştırmada yöntem olarak saha çalışması ve derinlemesine görüşme tekniği kullanılmıştır Çalışmanın varsayımı belediye destekli canlandırma projesinin yerel ekonominin canlandıracağı ve yaşanan dönüşümün yerel esnaf tarafından olumlu karşılanacağı yönünde kurulmuştur. Fakat araştırmanın bulguları yaşanan dönüşümün yerel esnaftaki izdüşümünün olumsuz olduğu yönündedir. Olumsuz algının temelinde mahallenin geleneksel değerlerinin yitirildiği, komşuluk ilişkilerinin zayıfladığı yönünde görüşler yatmaktadır. Dolayısıyla araştırma canlandırma projesinin sosyal sonuçlarını betimlemeyi ve verilen olumlu/olumsuz tepkilerin nasıl ifade edildiğini ve gerekçelendirildiğini gözler önüne sermektedir.
Modern İstanbul’da Mahalle’nin Dönüşen Anlamları